Alexander Sutherland Neill, Education, Joyful Learning - peavey, danniel; Aliyyah Sofie, Zerlinda (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2025)
Education plays a central role in shaping individuals’ character, critical awareness, and capacity to engage with society. Among educational thinkers, Alexander Sutherland Neill is notable for his advocacy of freedom- and democracy-based education as implemented in Summerhill School. This study aims to examine Neill’s educational philosophy, particularly the principles of learning without coercion, examinations, and punishment, and to analyze its relevance to the concept of Merdeka Belajar in the Indonesian educational context. This research employs a literature review method by analyzing Neill’s primary works and relevant scholarly articles related to democratic education and Merdeka Belajar policies. Data were analyzed using qualitative descriptive analysis through data collection, reduction, display, and conclusion drawing. The findings indicate that Neill’s emphasis on student autonomy, active participation, and respect for individual development aligns conceptually with the principles of Merdeka Belajar, which prioritize learner-centered, humanistic, and joyful learning. This study contributes theoretically by strengthening the philosophical foundation of Merdeka Belajar through classical democratic education perspectives and practically by offering insights for educators in implementing more emancipatory learning practices.